Penjaminan Mutu Satuan Pendidikan Muadalah Berbasis Undang-undang Pesantren - Ahmadi, Ahmadi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
research seeks to describe the quality assurance system in three Muadalah Education Units in Madura with a multi-case qualitative approach in three muadalah pesantren in Madura. Data sources are the managers of muadalah education units in Madura, from Kiai and teachers who are directly involved in quality assurance. With data validity checking techniques with extended observation, triangulation and peer examination. From the results of the study, it was found This that the managers of muadalah education units in Madura carry out quality assurance with two management models, namely first: attaching quality assurance to the structural duties of pesantren managers, and second, forming special work units as mandated by the Pesantren Law. From these two models, all muadalah education units in Madura make Kiai the main person responsible for the quality of the pesantren. The implementation of quality assurance in Muadalah Education Units in Madura has an impact on maintaining the education system of education with the uniqueness of each pesantren, as well as many outstanding santri in various competitions.